2021
DOI: 10.1007/s11357-021-00424-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on ischemic stroke care in Hungary

Abstract: Data about the coronavirus disease 2019 (COVID-19) pandemic’s collateral damage on ischemic stroke (IS) care during the second epidemic wave in Central Europe are limited. We sought to evaluate the impact of the COVID-19 outbreak on Hungarian IS care during the two epidemic waves. This retrospective observational study was based on a nationwide reimbursement database that encompasses all IS admissions and all reperfusion interventions, i.e., intravenous thrombolysis (IVT) and endovascular therapy (EVT) from 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“… 8 A study from Hungary demonstrated that both intravenous thrombolysis and endovascular therapy rates declined, but that the specific temporal pattern in these stroke therapies fluctuated over surges in the pandemic. 34 A study from the United Kingdom indicated that quality of care was preserved during the pandemic. 32 Our results are similar to those from a study of stroke care quality in Taiwan that also reported higher quality rates during the COVID-19 pandemic as compared to the pre-COVID-19 period.…”
Section: Discussionmentioning
confidence: 99%
“… 8 A study from Hungary demonstrated that both intravenous thrombolysis and endovascular therapy rates declined, but that the specific temporal pattern in these stroke therapies fluctuated over surges in the pandemic. 34 A study from the United Kingdom indicated that quality of care was preserved during the pandemic. 32 Our results are similar to those from a study of stroke care quality in Taiwan that also reported higher quality rates during the COVID-19 pandemic as compared to the pre-COVID-19 period.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a noticeable drop in acute stroke hospitalization and acute reperfusion therapy numbers during the pandemic worldwide [ 33 , 35 , 45 51 ] as well as in Hungary [ 52 , 53 ]. In the COVID-19 pandemic era, it is a struggle to harmonize the obligatory containment restrictions for COVID-19 and the “time is brain” concept of acute reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by the analysis from Bojti et al [ 20 ], we examined if similar situations occurred at two distinct medical institutions in the USA: Northwestern Memorial Hospital Comprehensive Stroke Center, Chicago, IL, and Oklahoma City Veterans Affairs Medical Center, Oklahoma City, OK. For the first institution, raw data was converted to standardized z -scores to compare across periods, as done by Bojti et al We considered z -scores of magnitude 2 or greater to represent statistically significant deviations in case numbers at a given time point relative to the entire time period of comparison. For the second institution, we used the Mann–Kendall test for monotonic trend, with significance set at 0.05.…”
Section: Analysis Of Changes In Ischemic Stroke Care At Two Distinct ...mentioning
confidence: 99%
“…After the first wave of COVID-19 (spring 2020) subsided in various regions around the world, these anecdotal reports of reduced acute presentations for stroke were confirmed by multiple separate groups [ 15 – 19 ]. The recent publication by Bojti et al [ 20 ] in Geroscience is unique among these reports in that they provide additional insight by presenting specific data from several years of pre-pandemic acute stroke admissions, cases from multiple consecutive COVID-19 waves, and corresponding public health mandates that were implemented in an effort to mitigate COVID-19 associated morbidity. The national scope of these data suggests that the study results and potential public health lessons are likely to generalize to similar socioeconomic settings outside of Hungary, where Bojti et al [ 20 ] conducted their study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation